Capsular polysaccharide of Streptococcus agalactiae is an essential virulence factor for infection in Nile tilapia (Oreochromis niloticus Linn.) - Zhang, Defeng (Journal of fish diseases, 2019)
© 2018 John Wiley & Sons Ltd.